NATURAL GAS COMBUSTION INSIDE A CONFINED VOLUME CHAMBER USING GAS-JET IGNITION METHOD - Fawzi, Mas; Kidoguchi, Yoshiyuki (Journal of Advanced Manufacturing Technology (JAMT), 2015)
The demand for natural gas is increasing since recent climate change. Natural gas is considered an abundant energy source with low greenhouse-gas emissions. A natural gas engine usually operates in lean-burn mode to gain the advantage of high thermal efficiency and low nitrogen oxides emission. Aproblem typically associated with natural gas combustion in lean mode is poor ignitability. The objective of this study is to improve ignitability of lean natural gas combustion using gas-jet ignition method. Several experiments were done using a confined volume chamber apparatus. Images of the combustion flame were captured using a high speed camera, and hydrocarbon emissions were measured. The result showed that the gas-jet ignition method is effective in improving ignitability of lean natural gas mixture. A addition of 30% hydrogen gas to the natural gas fuel improves both the ignitability and further flame propagation, thus lowering the hydrocarbon emission.